Navigating COVID-19 Pandemic and Building Resilience: A Case Study of Al-Furat Al-Awsat Technical University ATU - Al-Zuhairy, Mudhaffar S.; Al-Zaini, Essam O. (Journal of Sustainability Perspectives, 2022)
The COVID-19 pandemic has created the largest disruption of education systems and, in particular, the higher education system in human history. Social distancing and restrictive movement policies have significantly disturbed traditional educational practices. Indeed, such disruption will not be the last to impact the continuity of higher education has led to an interest in the concept of institutional resilience. Also, returning to the original operation state of universities campuses after relaxation of restriction is another challenge with many new standard operating procedures. Like almost all other academic institutions, Al-Furat Al-Awsat Technical university ATU provides people with professional and personal skills and capabilities. ATU has access to a remarkable number of young and curious people who are passionate, creative, and desire a better world. ATU, therefore, needs to ensure equipping current and future leaders, decision-makers, teachers, and innovators with the knowledge, skills, and motivation towards facing such unpredictable challenges. The current article highlights in-depth five steps undertaken by ATU university’s leader to improve the university's complicated infrastructure systems to building resilience and withstanding current and futuristic distributions.Keyword: ATU-resilience, ATU- infrastructure, COVID-19 Pandemic